Repair of Tetralogy of Fallot in Cameroonian Children: Report of 105 cases - Mve Mvondo, Charles; Ngo Yon, Laurence Carole; Kobe, Zephanie Fokalbo; Tsague Kengni, Hermann Nestor; Banga Nkomo, Douglas; Lowe Kuissu, Sepolin; Metogo Bengono, Junette; Ndobo Nkoe, Valerie; Ela Bella, Amos; Tchantchou Tchoumi, Cabral; Yepmo, Yannick; Ngatchou Djomo, William; et al. (HEALTH SCIENCES AND DISEASE, 2024)
ABSTRACT Background. Delayed diagnosis of congenital heart diseases is common in children living in low- to middle-income countries due to limited access to cardiovascular care. Late diagnosis of tetralogy of Fallot (ToF) often leads to the presentation of complex clinical features, significantly affecting surgical outcomes. This paper aims to review the operative mortality following surgical treatment of African children with ToF over a 12-year period. Materials and Methods. Between November 2009 and December 2021, a total of 105 children diagnosed with ToF underwent surgical intervention at our institution. Clinical, echocardiographic, and surgical data were retrospectively reviewed. Results. The median age at surgery was 36 months (IQR: 20–72 months). The sex ratio was 1.39 (male to female). The primary symptoms reported were fatigue (16.2%, n = 17/105), cyanosis (7.6%, n = 8/105), or a combination of both (76.2%, n = 80/105). The vast majority (95.2%, n = 100/105) underwent a total ToF correction. The transatrial-approach for ventricular defect (VSD) closure was performed in 92.3% of cases (n = 97/105). Transanular and/or infundibular patches were used in 89 (84.8%) patients. Postoperative complications included respiratory distress in 5 (4.8%) patients and reexploration for bleeding in 6 (5.75%) patients. The operative mortality rate was 5.7% (n = 6/105). Conclusion. Despite the increased age and more complex pathophysiological features, surgical treatment of children with ToF in our setting is associated with acceptable early outcomes. Timely screening and surgical correction before the onset of associated complications are advocated as crucial measures to mitigate surgical risks. RÉSUMÉ Introduction. Le retard de diagnostic des cardiopathies congénitales est fréquent chez les enfants vivant dans les pays à revenus faibles ou moyens, en raison de l’accès limité aux soins cardiovasculaires. Le diagnostic tardif de la tétralogie de Fallot (TdF) conduit souvent à l’apparition de caractéristiques cliniques complexes, ce qui affecte de manière significative les résultats chirurgicaux. Cet article a pour but d’examiner la mortalité opératoire suite au traitement chirurgical des enfants africains atteints de ToF sur une période de 12 ans. Matériels et méthodes. Entre novembre 2009 et décembre 2021, un total de 105 enfants diagnostiqués avec une TdF ont subi une intervention chirurgicale dans notre institution. Les données cliniques, échocardiographiques et chirurgicales ont été revues rétrospectivement. Résultats. L’âge médian au moment de l’intervention chirurgicale était de 36 mois (IQR : 20-72). Le sex-ratio était de 1,39 (hommes/femmes). Les principaux symptômes signalés étaient la fatigue (16,2 %, n = 17/105), la cyanose (7,6 %, n = 8/105) ou une combinaison des deux (76,2 %, n = 80/105). La grande majorité (95,2 %, n = 100/105) a subi une correction totale de la ToF. L’approche transatriale pour la fermeture du défaut ventriculaire a été réalisée dans 92,3 % des cas (n = 97/105). Des patchs transannulaires et/ou infundibulaires ont été utilisés chez 89 patients (84,8 %). Les complications postopératoires comprenaient une détresse respiratoire chez 5 (4,8 %) patients et une réexploration pour hémorragie chez 6 (5,75 %) patients. Le taux de mortalité opératoire était de 5,7 % (n = 6/105). Conclusion. Malgré l’âge élevé et les caractéristiques physiopathologiques plus complexes, le traitement chirurgical des enfants atteints de TdF dans notre contexte est associé à des résultats précoces acceptables. Un dépistage opportun et une correction chirurgicale avant l’apparition des complications associées sont préconisés comme des mesures cruciales pour réduire les risques chirurgicaux.